The Role Of Social Nursing In Improving Public Health - Wawan Kurniawan (Journal Of Social Science (JoSS), 2022)
Health has an important role in carrying out daily activities comfortably and safely. Without health, life becomes less effective and efficient because whatever is done to humans depends on their level of health. One way that is considered capable of improving public health is through social nursing that goes directly to the community. Therefore, researchers want to carry out research on the role of social nursing in improving public health. The purpose of this study was to determine whether or not the role of social nursing in improving public health. The research method used is descriptive qualitative with data collection through interviews, observations, and documentation to 50 respondents in city X. The results show that social nursing has a fairly large role, namely 70% in improving public health with various programs it does such as waste management, re-functioning water sewers, conducting weekly mutual assistance, clean food awareness movements, self-care awareness movements, and literacy awareness movements.